Biomechanical Testing of Spinal Segment Fixed by Arcofix System on the Swine Spine - Kelbl, Martin; Kocis, Jan; Vesely, Radek; Florian, Zdenek; Navrat, Tomas; Vosynek, Petr (Asian spine journal, 2015)
STUDY DESIGN: An in vitro biomechanical study. PURPOSE: To evaluate the mechanical properties of the spinal segment in the intact, injured, and stabilized state after fixation by an Arcofix implant. OVERVIEW OF LITERATURE: Several types of thoracolumbar spine injury necessitates anterior instrumentation. The Arcofix plate represents the latest generation of angular stablity systems. The biomechanical properties of these implants have not been sufficiently studied yet. METHODS: A total of ten porcine specimens (levels Th12-L3) were prepared. The tests were performed for intact, injured, and implanted specimens. In each state, the specimen was subjected to a tension load of a prescribed force, and subsequently, twisted by a given angle. The force load was 200 N. The torsion load had a deformation character, i.e., the control variable was the twisting angle and the measured variable was the moment of a couple. The amplitude of the load alternating cycle was 3°. Another parameter that was evaluated was the area of the hysteresis loop. The area corresponds to the deformation energy which is dissipated during the cycle. RESULTS: A statistically significant difference was found between the intact and injured states as well as between the injured and implanted specimens. The statistical evaluation also showed a statistically different value of the hysteresis loop area. In the case of instability, the area decreased to 33% of the physiological value. For the implanted sample, the area increased to 170% of the physiological value. CONCLUSIONS: The Arcofix implant with its parameters appears to be suitable and sufficiently stable for the treatment of the anterior column of the spine.
Keywords: Anterior stabilization; Spine stabilization; Biomechanics; Thoracolumbar fracture